2022
DOI: 10.3390/molecules27217366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polyhydroxybutyrate, PHB, Synthesized by Newly Isolated Haloarchaea Halolamina spp.

Abstract: This work aims to characterize the haloarchaeal diversity of unexplored environmental salty samples from a hypersaline environment on the southern coast of Jeddah, Saudi Arabia, looking for new isolates able to produce polyhydroxyalkanoates (PHAs). Thus, the list of PHA producers has been extended by describing two species of Halolamina; Halolamina sediminis sp. strain NRS_35 and unclassified Halolamina sp. strain NRS_38. The growth and PHA-production were investigated in the presence of different carbon sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Within the range of 1000 to 1300 cm −1 , a series of pronounced bands signifies the stretching of the (C-O) bond inherent to the ester group. Importantly, all these spectral features align closely with the standard commercial polyhydroxybutirate (Sigma-Aldrich) (Figure 6); therefore, it is confirmed that the polymeric extract studied is a short chain named polyhydroxybutyrate (PHB) [29,62].…”
Section: Optimization Of Phb Production and Kinetic Studiessupporting
confidence: 69%
“…Within the range of 1000 to 1300 cm −1 , a series of pronounced bands signifies the stretching of the (C-O) bond inherent to the ester group. Importantly, all these spectral features align closely with the standard commercial polyhydroxybutirate (Sigma-Aldrich) (Figure 6); therefore, it is confirmed that the polymeric extract studied is a short chain named polyhydroxybutyrate (PHB) [29,62].…”
Section: Optimization Of Phb Production and Kinetic Studiessupporting
confidence: 69%
“…The polymer extracted from 2D1 was analyzed by FTIR analysis in a frequency range of 400 to 4000 wave number cm −1 to identify the functional groups of the extract (Figure 9). For the 2D1 extract (Figure 9a), a wide range of the absorption peak was observed at 3445 cm −1 , indicating the presence of -OH group bonds, followed by a second transmittance peak at 2927 cm −1 , generally related to the symmetric C-H stretching of the CH 2 groups of fatty acids [51]. The sharp peak at 1726 corresponded to the C=O ester group characteristic of PHB, while the short peak at 1270 cm −1 indicated the presence of CH groups [61,62].…”
Section: Chemical Characterization By Fourier Transform Infrared Spec...mentioning
confidence: 99%
“…The greater optical density corresponded to a higher cell density in the culture, which can suggest a greater amount of putative PHB accumulated by the cells [32]. With this expectation in mind, it was necessary to explore the other variables: NaCl concentration, pH, nitrogen sources, argan residue concentration, and different culture volumes for a more efficient growth and productivity of 2D1 [51]. Besides the determination of the optimal temperature and incubation time for the species 2D1, the DCW and PHB measured confirmed the species capacity on the putative PHB accumulation by using argan seed waste, as earlier reported in Table 2.…”
Section: Effect Of Temperature and Incubation Timementioning
confidence: 99%
See 1 more Smart Citation
“…Besides, some haloarchaea can be used in the bioremediation processes to remove heavy metals and inorganic anions from brines and salty water (Oren, 2010;Nájera-Fernández et al, 2012;Martínez-Espinosa et al, 2015;Hou and Cui, 2018;Zuo et al, 2018;Pacholak et al, 2021;Pfeifer et al, 2021;Martínez et al, 2022;Moopantakath et al, 2023). Within haloarchaea, the most promising microorganism is Haloferax mediterranei (Pfeifer et al, 2021;Hagagy et al, 2022;Costa et al, 2023;Diankristanti et al, 2023), because it can synthesize PHBV without using any HV precursor (as required by other microorganisms) and can use different carbon sources to accomplish it (Tan et al, 2014b;Han et al, 2015;Parroquin-Gonzalez and Winterburn, 2023). 10.3389/fmats.2024.1405483 The metabolic pathways that allow the production of PHA are diverse if they are analyzed and compared in all groups of microorganisms, but essentially, all of them share the following reactions.…”
Section: Biological Synthesis Of Phasmentioning
confidence: 99%